Earnings management and the performance of seasoned equity offerings1I gratefully acknowledge the comments and suggestions of Philip Berger, Patricia Dechow, Kenneth Gaver (the referee), Robert Holthausen, Wayne Mikkelson (the editor), and Richard Sloan. I also thank Andrew Alford, Brad Barber, Randolph Beatty, Ilia Dichev, Paul Fisher, Gary Gorton, Paul Griffin, David Larcker, Mark Low, Patricia O'Brien, Madhav Rajan, Jay Ritter, Mark Vargus, Robert Verrecchia, Franco Wong, and workshop participants at the 1996 American Accounting Association meetings, Columbia University, Emory University, INSEAD, London Business School, MIT, New York University, Northwestern University, Purdue University, University of California at Davis, University of Chicago, University of Michigan, University of Minnesota, University of Pennsylvania, and Yale University for useful comments. I am indebted to Mark Vargus for access to his FORTRAN sub-routines. Errors and omissions are my responsibility.1 - Rangan, Srinivasan (Journal of Financial Economics, 1998)
Recent studies document that firms conducting seasoned equity offerings experience poor stock price and earnings performance in the post-offering period. I investigate whether earnings management around the time of the offering can explain a portion of the poor performance. Consistent with this explanation, I show that earnings management during the year around the offering predicts both earnings changes and market-adjusted stock returns in the following year. These findings suggest that the stock market temporarily overvalues issuing firms and is subsequently disappointed by predictable declines in earnings caused by earnings management.